2017
DOI: 10.1177/1056789517734036
|View full text |Cite
|
Sign up to set email alerts
|

An elastic–plastic damage model considering capillary effect for petrol–water saturated sandstone

Abstract: The mechanical behavior of surrounding rock mass is key important to the water-sealed petrol storage caverns because of the two phase environment. To investigate the strength and damage mechanism of rock mass under petrol–water immersion circumstance, an elastic–plastic damage constitutive model is proposed. The deformation work of rock mass is derived according to the mixture theory and averaging methods. In order to further study the capillary action influence of petrol–water liquid phase on the strength and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…Recent years has witnessed extensive researches on the mechanical properties of coal rock under water interaction. For varying-MC coal rock samples (i.e., coal rock samples that contain varying contents of moisture), the quantitative relation between MC and macroscopic mechanical parameters (such as cohesion, elastic modulus, internal friction angle and uniaxial compressive strength) was obtained in uniaxial compression tests (Erguler and Ulusay, 2009; Hawkins and McConnell, 1992; Song et al., 2022; Yang et al., 2018; Yao et al., 2016) and shear tests (Li et al., 2020; Yao et al., 2020, 2021). It was found that the peak stress, internal friction angle, cohesion and elastic modulus decrease with the rise of MC; meanwhile, the tensile failure mode alters to the shear failure mode (Tang, 2018; Tang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Recent years has witnessed extensive researches on the mechanical properties of coal rock under water interaction. For varying-MC coal rock samples (i.e., coal rock samples that contain varying contents of moisture), the quantitative relation between MC and macroscopic mechanical parameters (such as cohesion, elastic modulus, internal friction angle and uniaxial compressive strength) was obtained in uniaxial compression tests (Erguler and Ulusay, 2009; Hawkins and McConnell, 1992; Song et al., 2022; Yang et al., 2018; Yao et al., 2016) and shear tests (Li et al., 2020; Yao et al., 2020, 2021). It was found that the peak stress, internal friction angle, cohesion and elastic modulus decrease with the rise of MC; meanwhile, the tensile failure mode alters to the shear failure mode (Tang, 2018; Tang et al., 2021).…”
Section: Introductionmentioning
confidence: 99%